Myostatin Knockout Regulates Bile Acid Metabolism by Promoting Bile Acid Synthesis in Cattle - Di Wu; Mingjuan Gu; Zhuying Wei; Chunling Bai; Guanghua Su; Xuefei Liu; Yuefang Zhao; Lei Yang; Guangpeng Li (Animals, 2022)
Myostatin (MSTN) is a major negative regulator of skeletal muscle mass and causes a variety of metabolic changes. However, the effect of MSTN knockout on bile acid metabolism has rarely been reported. In this study, the physiological and biochemical alterations of serum in MSTN+/− and wild type (WT) cattle were investigated. There were no significant changes in liver and kidney biochemical indexes. However, compared with the WT cattle, lactate dehydrogenase, total bile acid (TBA), cholesterol, and high-density lipoprotein (HDL) in the MSTN+/− cattle were significantly increased, and glucose, low-density lipoprotein (LDL), and triglycerides (TG) were significantly decreased, indicating that MSTN knockout affected glucose and lipid metabolism and total bile acids content. Targeted metabolomic analysis of the bile acids and their derivatives was performed on serum samples and found that bile acids were significantly increased in the MSTN+/− cattle compared with the WT cattle. As the only bile acid synthesis organ in the body, we performed metabolomic analysis on the liver to study the effect of MSTN knockout on hepatic metabolism. Metabolic pathway enrichment analysis of differential metabolites showed significant enrichment of the primary bile acid biosynthesis and bile secretion pathway in the MSTN+/− cattle. Targeted metabolomics data further showed that MSTN knockout significantly increased bile acid content in the liver, which may have resulted from enhanced bile acid synthesis due to the expression of bile acid synthesis genes, cholesterol 7 alpha-hydroxylase (CYP7A1) and sterol 27-hydroxylase (CYP27A1), and upregulation in the liver of the MSTN+/− cattle. These results indicate that MSTN knockout does not adversely affect bovine fitness but regulates bile acid metabolism via enhanced bile acid synthesis. This further suggests a role of MSTN in regulating metabolism.